2018
DOI: 10.1007/s10461-018-2125-2
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Discontinuation May Diminish PrEP Coverage Among Young Men Who Have Sex with Men

Abstract: Understanding pre-exposure prophylaxis (PrEP) discontinuation is key to maximizing its effectiveness at the individual and population levels. Data came from the RADAR cohort study of MSM aged 16-29 years, 2015-2017. Participants included those who reported past 6-month PrEP use and discontinued its use by the interview date. Of the 197 participants who had used PrEP in the past 6 months, 65 discontinued use. Primary reasons for PrEP discontinuation included trouble getting to doctor's appointments (14, 21.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 7 publications
1
63
1
Order By: Relevance
“…Persistence (i.e., continuing to take PrEP while the adolescent remains at risk for acquiring HIV) is another important factor. A study of young MSM (aged 16-29 years) reported that 33% of 197 males who reported using PrEP in the past 6 months had discontinued PrEP by the time of the study interview (94). The most commonly reported reasons for discontinuing PrEP included difficulty getting to appointments, lapse in insurance coverage, and perception of being no longer at risk for HIV (94).…”
Section: Medication Initiation Adherence and Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Persistence (i.e., continuing to take PrEP while the adolescent remains at risk for acquiring HIV) is another important factor. A study of young MSM (aged 16-29 years) reported that 33% of 197 males who reported using PrEP in the past 6 months had discontinued PrEP by the time of the study interview (94). The most commonly reported reasons for discontinuing PrEP included difficulty getting to appointments, lapse in insurance coverage, and perception of being no longer at risk for HIV (94).…”
Section: Medication Initiation Adherence and Persistencementioning
confidence: 99%
“…A study of young MSM (aged 16-29 years) reported that 33% of 197 males who reported using PrEP in the past 6 months had discontinued PrEP by the time of the study interview (94). The most commonly reported reasons for discontinuing PrEP included difficulty getting to appointments, lapse in insurance coverage, and perception of being no longer at risk for HIV (94). Regular screening for the need and desire to continue with PrEP is part of the ongoing care of an adolescent prescribed PrEP.…”
Section: Medication Initiation Adherence and Persistencementioning
confidence: 99%
“…After PrEP initiation, safe and effective use depends on adherence to the medication, retention in routine PrEP medical monitoring, and consistent use during periods of high-risk behaviors. Difficulty adhering to these behaviors contributes to reduced protection against HIV infection among BLMSM and BLTW PrEP users [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, discontinuations of PrEP use among individuals with ongoing risks for acquiring HIV could decrease the effectiveness of PrEP [10,11]. Observational studies of PrEP prescribing in healthcare settings have demonstrated that many patients who initiate PrEP subsequently discontinue its use [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%